ChemInform Abstract: N‐Aryl Modification in γ‐Lactam: Design and Synthesis of Novel Monocyclic γ‐Lactam Derivatives as Inhibitor for Bacterial Propagation. Issue 1 (3rd January 2013) - Patra, Prasanta; Kar, Gandhi K.; Sarkar, Aparna; Ray, Jayanta K.; Dasgupta, Tista; Ghosh, Mahua; Bhattacharya, Sugata
Abstract A series γ‐lactams of type (V), (VI), (VIII), (X), or (XI) are prepared.